Assessing Seasonal Changes in Physicochemical Traits and Biochemical Profiles of Key Carp Species in Masani Barrage Lake and JLN Canal - Yadav, Sonal; Kumar, Naveen (International Journal of Membrane Science and Technology, 2023)
Our thorough seasonal analysis of Masani Barrage Lake and JLN Canal in Rewari reveals the profound impact of seasonal changes on aquatic ecosystems. Both water bodies display distinct patterns in temperature, pH, salinity, and other parameters. The unique characteristics of lakes, with greater temperature fluctuations and nutrient cycling, contribute to differences in phytozooplankton and ecological dynamics compared to more regulated canals. Additionally, our study on common carp tissues shows clear seasonal variations in moisture, ash, protein, lipid, and fatty acid levels, indicating specific metabolic responses to environmental conditions. Understanding these nuances is crucial for grasping the diverse influences of these habitats on fish physiology, with lakes experiencing more significant variations than canals due to their larger and more open systems.